Confined masonry in seismic regions: Application to a prototype building in nepal. (January 2023) - Acharya, Ojaswi; Dahal, Aarosh; Shrestha, Kshitij C.
Abstract: Confined Masonry (CM) has emerged as an economical and viable construction technique, which is practiced in many seismically vulnerable zones around the world. Despite having performed well during past earthquakes, many seismically prone areas such as Nepal are reluctant to adopt confined masonry as a reliable method of building construction due to limited number of works in understanding its behavior under earthquake loading in comparison to more accepted construction such as RC frame structures and even lesser number of works comparing the behavior of full-fledged building models. Also, modeling of CM buildings still is not commonplace. The objective of this study is to validate a numerical model with the experimental results and to compare the features of the confined masonry thus modeled from a validated process with reinforced concrete construction in terms of seismic behavior and cost of construction in the scenario of Nepal. To attain this objective, the finite element models are developed for confined masonry wall panels which are validated using experimental results from existing works of literature. Then finite element models of prototypical confined masonry and reinforced concrete buildings, using locally available material properties, were developed so as to study the behavior of both under seismic loading by performing pushover analysis and preparing fragility curves. Moreover, a parametric study is performed to study the influence of critical parameters on the overall behavior of the building models. Finally, with the help of the results obtained, CM building has been established as a technically and economically viable building practice in seismically vulnerable areas.